We have to solve 3*cos(3x - 1) = 0 for x.

3*cos(3x - 1) = 0

=> cos(3x - 1) = 0

=> 3x - 1 = arc cos 0

=> 3x - 1 = pi/2 + 2*n*pi and 3x - 1 = 3*pi/2 + 2*n*pi

=> 3x = pi/2 +1 + 2*n*pi and 3x = 3*pi/2 + 1 + 2*n*pi

=> x = pi/6 +1/3 + 2*n*pi/3 and x = pi/2 + 1/3 + 2*n*pi/3

**The required solution is x = pi/6 +1/3 + 2*n*pi/3 and x = pi/2 + 1/3 + 2*n*pi/3**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.